Experience obtaining legal abortion in Uruguay: knowledge, attitudes, and stigma among abortion clients - Shelly Makleff; Ana Labandera; Fernanda Chiribao; Jennifer Friedman; Roosbelinda Cardenas; Eleuthera Sa; Sarah E. Baum (BMC, 2019)
Abstract Background The abortion law in Uruguay changed in 2012 to allow first trimester abortion on request. Implementation of the law in Uruguay has been lauded, but barriers to care, including abortion stigma, remain. This study aimed to assess women's experiences seeking abortion services and related attitudes and knowledge following implementation of the law in Uruguay. Methods We interviewed 207 eligible women seeking abortion services at a high-volume public hospital in Montevideo in 2014. We generated univariate frequencies to describe women's experiences in care. We conducted regression analysis to examine variations in experiences of stigma by women's age and number of abortions. Results Most of the women felt that abortion was a right, were satisfied with the services they received, and agreed with the abortion law. However, 70% found the five-day waiting period unnecessary. Women experienced greater self-judgement than worries about being judged by others. Younger women in the sample (ages 18-21) reported being more worried about judgment than women 22 years or older (1.02 vs. 0.71 on the ILAS sub-scale). One quarter of participants reported feeling judged while obtaining services. Women with more than one abortion had nearly three times the odds of reporting feeling judged. Conclusions These findings highlight the need to address abortion stigma even after the law is changed. Some considerations from Uruguay that may be relevant to other jurisdictions reforming abortion laws include: the need for strategies to reduce judgmental behavior from staff and clinicians towards women seeking abortions, including training in counseling skills and empathic communication; addressing stigmatizing attitudes about abortion through community outreach or communications campaigns; mitigating the potential stigma that may be perpetuated through policies to prevent "repeat" abortions; ensuring that younger women and those with more than one abortion feel welcome and are not mistreated during care; and assessing the necessity of a waiting period. The rapid implementation of legal, voluntary abortion services in Uruguay can serve in many ways as an exemplar, and these findings may inform the process of abortion law reform in other countries.